Social workers' adaptation in times of pandemic crisis: A Hong Kong case. (January 2023) - Ling, Henry Wai Hang; Shum, Michelle; Kwan, Chi Kin; Xu, Mingdie
Through the lens of the theory of planned behavior, this article explores how social workers adapt to a new situation due to the outbreak of the COVID-19 pandemic. Three focus group sessions were conducted with 23 social workers from child and youth, family, and elderly services in Hong Kong. Three major themes were generated: (1) repositioning the social work profession, (2) renegotiating contracts with funders, and (3) exploring novel intervention methods. Implications of the findings are discussed. To ensure social workers can respond effectively in crises, an evolving nature of the profession is advocated to enshrine its spirit to serve.